Dampak Penggunaan Android Terhadap Aktivitas Pembelajaran Pada Mahasiswa Manajemen Pendidikan Islam Universitas Islam Negeri Sumatera Utara - Hasana Fadillah; Maya Masita; Sri Rahayu Ningsih; Alfieridho Alfieridho; Ahmadi Hamsa Ramadhan; Muhammad Al-Fatih; Arina Denggan Munthe; Sri Mulyani; Ayyu Purnama; Maulana Yontino; Maulida Tri Puspita; Luthfia Farhana; Muhammad Kurniawan Lubis; Nurul Bayani; Nurul Zahara Bancin; Renilda Putri Salam; Afrida Yanti; Zoe Zarka Syafiq; Dimas Andika Saputra (Institut Nalanda, 2023)
Developments in the field of information and communication technology have produced various products. One of the results of this development is Android-based smartphones. The development of smartphones themselves has been used in the field of education, smartphones are used as learning media. This learning media is usually available in the form of an application that can be downloaded on the Play Store or Google Play. However, can this application produce learning media that is fun, effective and not boring or can this application overcome learning difficulties? This research, which aims to determine the effect of Android application-based learning media on students' interest in learning, will use quantitative research methods with analytical methods using simple linear regression analysis. Based on the results of data analysis and discussions carried out by researchers, it can be concluded that there is a large influence of Android application-based learning media on the interest in independent learning of Islamic Religious Education students at the Islamic University of Indonesia. This is proven by the results of a simple linear regression analysis test carried out, the test results show that the price or value of Android application-based media has a big influence on students' interest in independent learning. The influence of learning media proves that media is one of the factors that influences interest in learning. This research aims to find out the benefits of smartphones as a learning medium for Islamic education management and what applications can be used in learning media. This research is a type of qualitative descriptive research conducted by interviews. Data analysis used is in the form of data collection and data presentation.